Construction Project Progress Evaluation Using a Quantitative Approach by Considering Time, Cost and Quality - Kurniady, Dedy Achmad; Nurochim, Nurochim; Komariah, Aan; Turwelis, Turwelis; Tan Hoi, Huynh; Hoang Ca, Vo (International Journal of Industrial Engineering and Management, 2022)
Examining the progress of the project and comparing it with the planned values removes many ambiguities for project management. In this article, a new quantities framework is proposed to evaluate the progress of construction projects with considering different risks. The work progress status (WPS) performance improvement method is based on the performance of input indicators, time, work progress, cost, and two key performance indicators, namely Stakeholder satisfaction performance index and Quality performance index. After the implementation of each step, the actual values of the input factors are identified and compared with the initial program. Results allow project managers to examine the impact of WPS performance on those that have not yet been performed. Article history: Received (November 23, 2021); Revised (January 01, 2022); Accepted (January 13, 2022); Published online (February 14, 2022)